The Urgency of Integrating Customary Sanctions in the National Criminal System as a Form of Restorative Justice in Biak Numfor Based on Law Number 1 of 2023 concerning the Criminal Code. - anwar, iryana; Ar Rasyid, Yanuriansyah; Djamaludin, Djamaludin; Lubis, Ahmad Hisyam (Universitas Islam kadiri, 2025)
This research aims to analyze the legal arrangements regarding the recognition of the law that lives in society in the 2023 Criminal Code (KUHP) and examine the urgency of integrating customary sanctions in the national penal system, especially in Biak Numfor Regency, as a manifestation of restorative justice. The research method used is normative-empirical legal research, with a legislative, conceptual, and sociological approach, through literature study and analysis of customary case settlement practices in Biak Numfor. The results of the study show that normatively, Article 2 of the 2023 Criminal Code provides a clear legal basis for the recognition of living law as a source of national criminal law. Philosophically, the recognition is in line with the values of Pancasila, the theory of Volksgeist Savigny, and the principle of restorative justice that emphasizes the restoration of social relations. Meanwhile, sociologically, customary settlement practices in Biak Numfor have proven effective in creating peace, strengthening legal legitimacy, and reducing the burden of formal justice. This study emphasizes that the integration of customary sanctions into the national penal system is a strategic step towards a legal system that is humanistic, socially just, and rooted in the local values of Indonesian society.